Eltrombopag for Delayed Platelet Recovery and Secondary Thrombocytopenia Following Allogeneic Stem Cell Transplantation in Children. Issue 1 (January 2019) - Li, Sidan; Wu, Runhui; Wang, Bin; Fu, Lingling; Zhu, Guanghua; Zhou, Xuan; Ma, Jie; Zhang, Liqiang; Qin, Maoquan
Abstract : The delay in platelet recovery after hematopoietic stem cell transplantation (HSCT) is closely related to the overall survival rate of transplanted children. The use of platelet-producing agents such as eltrombopag and romiplostim has made great progress in treating diseases such as immune thrombocytopenia and aplastic anemia. However, the use of such drugs in patients with thrombocytopenia after transplantation, especially in children, is rare. This study aimed to report eltrombopag treatment for 3 children with primary platelet engraftment failure and secondary thrombocytopenia after allogeneic HSCT. Of these patients, 2 had platelets stabilized at ≥50×10 9 /L after eltrombopag treatment and subsequent withdrawal of eltrombopag. All 3 patients showed no clear adverse reactions. The results indicated a wide application prospect of eltrombopag treatment in children with thrombocytopenia after allogeneic HSCT.